Saponins of Dipsacus Azureus Plant and Their Hypoglycemic Activity - Аkramov D.Kh; Jabbarov Sh.A; Almasova S.J; Urinova L.A; Аshurova L.N (Genius Journals, 2023)
The genus Dipsacus belongs to the family Dipsacaceae, represented by 92 species worldwide, of which 2 species grow in Uzbekistan: D. laciniatus (L) and D. azureus (Schrenk) [1-2]. The perennial herbaceous plant Dipsacus azureus Schrenk (azure hairweed) belongs to the Dipsacaceae family, distributed mainly along the northern slope of the Kyrgyz Ala-Too ridge in the Chui region, in Uzbekistan in the Tashkent, Fergana, Surkhandarya, Samarkand and Andijan regions
Keywords: Dipsacaceae; herbaceous plant